The Environmental Impacts of Protected Area Policy - Mathias Reynaert; Eduardo Souza-Rodrigues; Arthur A. van Benthem (Center for Economic Studies and ifo Institute (CESifo), 2023)
The world has pledged to protect 30 percent of its land and waters by 2030 to halt the rapid deterioration of critical ecosystems. We summarize the state of knowledge about the impacts of protected area policies, with a focus on deforestation and vegetation cover. We discuss critical issues around data and measurement, identify the most commonly-used empirical methods, and summarize empirical evidence across multiple regions of the world. In most cases, protection has had at most a modest impact on forest cover, with stronger effects in areas that face pressure of economic development. We then identify several open areas for research to advance our understanding of the effectiveness of protected area policies: the use of promising recent econometric advancements, shifting focus to direct measures of biodiversity, filling the knowledge gap on the effect of protected area policy in advanced economies, investigating the long-run impacts of protection, and understanding its equilibrium effects.
Keywords: Q23; Q24; Q57; R14; 330; protected areas; land protection; deforestation; biodiversity